Pick-Your-Own Labor: Migrant Workers and Flexibility in Canadian Agriculture1 - Preibisch, Kerry (International Migration Review, 2010)
This paper explores the structures and practices of temporary migrant worker programs (TMWP) as they operate in Canadian agriculture. Acting within highly competitive, globalized markets, agri-food employers rely on the availability of migrant workers to achieve greater flexibility in their labor arrangements, drawing on employment practices beyond those possible with a domestic workforce. Most recently, changes to Canada’s two TMWP schemes have provided employers with greater scope to shape the social composition of their workforce. The paper analyzes these changes while exploring their implications for workplace regimes in agriculture.